PENYELESAIAN SENGKETA ANTARA BUMN DENGAN PEMERINTAH DAERAH DALAM PENGELOLAAN ASET DAERAH - Ramadhan, Azar (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACTLand and/or building sale and purchase transactions are inseparable from the existence of an agreement/contract, where there is an agreement between the parties that bind themselves to each other, with one party submitting an object, and the other party will make a payment as previously agreed, as stipulated in Article 1457 of the Civil Code. Default from the seller also often occurs in land rights sale and purchase agreements which then cause losses to the buyer such as the inability to transfer the identity of land ownership rights from the seller to the buyer. This research is a type of Normative research that uses Secondary data sources and analyzes data using qualitative analysis methods in the form of sentence descriptions that are easy for readers to understand. Based on the results of the study, the Deed of Land Sale and Purchase Agreement in practice is often made in the form of an authentic deed made before a Notary, so that the Deed of Sale and Purchase Agreement is an authentic deed that has perfect evidentiary power. This is intended by the parties to provide more protection and legal certainty for the parties who make it. Because the notary in making the deed is impartial and maintains the interests of the parties objectively. That the sale and purchase agreement is a preliminary agreement, but there is a possibility that implementing all the requirements agreed upon in the sale and purchase agreement may take a long time, so there is also a possibility that the prospective seller is prevented from signing the sale and purchase deed (AJB). This will certainly cause difficulties for the buyer because the transfer of rights cannot be carried out even though the buyer has fulfilled all obligations to obtain his rights as agreed in the sale and purchase agreement. As for legal protection for the parties, especially buyers in a sale and purchase agreement made underhand, the legal protection provided in the sale and purchase agreement is very strong because of the evidentiary nature of the sale and purchase agreement made before a public official in this case a Notary.Keywords: Buyer, Land Rights, PPJB Deed, Notary.